Exploring the Role of Antithrombin in Nephrotic Syndrome–Associated Hypercoagulopathy: A Multi-Cohort Study and Meta-Analysis. Issue 2 (February 2023) - Abdelghani, Eman; Waller, Amanda P.; Wolfgang, Katelyn J.; Stanek, Joseph R.; Parikh, Samir V.; Rovin, Brad H.; Smoyer, William E.; Kerlin, Bryce A.
Visual Abstract: Abstract : Background: Nephrotic syndrome is associated with an acquired hypercoagulopathy that is thought to drive its predisposition for venous thromboembolism. Previous studies have suggested that urinary antithrombin (AT) loss leading to acquired AT deficiency is the primary mechanism underlying this hypercoagulopathy, but this hypothesis has not been directly tested. The objectives of this study were to test the influence of AT levels on hypercoagulopathy in nephrotic syndrome patient samples and perform meta-analyses to evaluate the likelihood of AT deficiency in patients with nephrotic syndrome. Methods: Samples from three independent nephrotic syndrome cohorts were analyzed. AT antigen and activity assays were performed using ELISA and amidolytic assays, respectively. Plasma thrombin generation, albumin, and urine protein-to-creatinine ratios were determined using established methods. Meta-analyses were performed by combining these new data with previously published data. Results: AT levels were not consistently related to either plasma albumin or proteinuria. AT was quantitatively related to hypercoagulopathy in adult nephrotic syndrome, whereas AT activity was inconsistently associated with hypercoagulopathy in childhood nephrotic syndrome. Notably, hypercoagulopathy did not differ between patients with normal AT levels and those with levels below the threshold used to define clinical AT deficiency (<70%). Moreover, ex vivo AT supplementation did not significantly alter hypercoagulopathy in AT-deficient plasma samples. The meta-analyses demonstrated that AT deficiency was not a uniform feature of nephrotic syndrome and was more common in children than adults. Conclusions: These data suggest that AT deficiency plays only a limited role in the mechanisms underlying the acquired hypercoagulopathy of nephrotic syndrome. Moreover, AT deficiency was not present in all patients with nephrotic syndrome and was more likely in children than adults despite the higher risk for venous thromboembolism in adults than children.